The type of metastasis is a prognostic factor in disseminated cervical cancer - Kim, Kidong; Cho, Soo Youn; Kim, Beob-Jong; Kim, Moon-Hong; Choi, Seok-Cheol; Ryu, Sang-Young (Journal of gynecologic oncology, 2010)
THE OBJECTIVES OF THIS STUDY WERE TWOFOLD: to verify whether the type of metastasis (lymphatic vs. hematogenous) is a prognostic factor, and to identify molecular markers associated with survival in patients with disseminated cervical cancer. Between April 1997 and May 2008, 30 patients with disseminated cervical cancer who had supraclavicular lymph node (N=13) or hematogenous metastases (N=17) were initially treated at our institute. We reviewed medical records to extract clinicopathologic variables. For 17 patients with available pathological specimens, we evaluated the association of immunohistochemical staining for metalloproteinase (MMP)-2, vascular endothelial growth factor (VEGF)-A, and laminin V gamma (LAMC)-2 with survival and clinicopathologic variables via a log-rank test and Cox regression analysis. Patients who had only lymphatic metastasis (odds ratio [OR], 5.3; 95% confidence interval [CI], 1.4 to 19.5) or completed initial treatment (OR, 3.2; 95% CI, 1.1 to 9.9) showed better survival than patients who did not, but none of the molecular markers were associated with survival. Out of 13 patients with only lymphatic metastasis, three patients who had received volume-directed radiation with concurrent chemotherapy had a long-term survival of over two years. However, patients with hematogenous metastasis showed extremely poor prognosis. The type of metastasis and completion of initial treatment were associated with prolonged survival in patients with disseminated cervical cancer, and over 20% of patients with lymphatic metastasis were salvaged with volume-directed radiation with concurrent chemotherapy. None of the molecular markers were associated with survival in patients with disseminated cervical cancer.